How Can We Use Simulation to Improve Competencies in Nursing? 2022
DOI: 10.1007/978-3-031-10399-5_2
|View full text |Cite
|
Sign up to set email alerts
|

How to Use Simulation as a Learning Method in Bachelor and Postgraduate/Master Education of Nurses and Teachers in Healthcare

Abstract: In this chapter, results from three different studies about simulation as a learning method are presented and discussed alongside relevant pedagogical theory and other research. These studies were conducted at a university in Norway from 2018 to 2020. The studies used a qualitative approach, and reflection notes and focus group interviews were used to collect data. The participants (81 students in total) were bachelor of nursing students 2nd year public health nursing students, and students in teacher training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The themes indicate that although each participant had undergone a unique experience based on their individual choices, they all had the same view-that the learning experience was more effective and enjoyable than that of their conventional class. Similar results were reported by Akselbo and Aune (2022) and Tawfik et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…The themes indicate that although each participant had undergone a unique experience based on their individual choices, they all had the same view-that the learning experience was more effective and enjoyable than that of their conventional class. Similar results were reported by Akselbo and Aune (2022) and Tawfik et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…Akselbo & Aune found that learners felt physical stress through a higher pulse and increased sweating [ 19 ]. However, this was perceived to help them better remember the skills learned in the simulation.…”
Section: Discussionmentioning
confidence: 99%
“…con "¿Los escenarios donde se desarrolla la simulación son realistas?" respaldándose por estudios que demuestran que, al proporcionar un mayor grado de realismo y seriedad, los estudiantes consiguen tomar mayor conciencia de la SCAF 21 . Además, aprenden a comunicarse, interactuar y administrar prioridades.…”
Section: Discussionunclassified
“…Li et al 22 , observaron mejoras en las habilidades interpersonales y el trabajo en equipo, incluyendo la colaboración, después de la imple-mentación de simulaciones de alta fidelidad en la formación de universitarios. Además, para que las simulaciones se perciban como herramientas de aprendizaje efectivas, es esencial que se cumplan ciertos requisitos como la capacitación del profesorado 21 , resaltando la importancia de su preparación para las simulaciones como herramientas de enseñanza.…”
Section: Discussionunclassified